Corporate governance in Singapore : evidence from straits times indexed companies and government-linked companies. - Fong, Baoyu. (2008)
This study examines the current compliance level in corporate governance disclosure of the top 50 Straits Times Indexed companies (STIs) and 18 Government-Linked Companies (GLCs) in Singapore.